Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Technology-Mediated Consumption on Identity: The case of Airbnb

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…For the guests who stayed in entire houses, host-guest communication mostly referred to help with some problems, such as check-in, without real social interaction. This explains why some studies have emphasized host-guest interaction as a key attribute [10,13], whereas others have proposed that the host is more like a facilitator than a friend.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the guests who stayed in entire houses, host-guest communication mostly referred to help with some problems, such as check-in, without real social interaction. This explains why some studies have emphasized host-guest interaction as a key attribute [10,13], whereas others have proposed that the host is more like a facilitator than a friend.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the development of the literature on how to improve guests' experience and satisfaction with P2P accommodations [7][8][9][10][11][12][13][14], these studies have focused on Western countries instead of those of Asia (China in particular). Cheng and Jin [9] suggested that context, such as the general multiculturality and safety of an environment, can influence the attributes of short-term rental experiences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impression management also takes place with respect to the service or good offered, especially when the contact between providers and consumers is limited. The objects and spaces represented will have to be desirable for the consumer (Ikkala & Lampinen, 2015) and project a positive light on their owners (Festila & Müller, 2017). The identities of the provider and of their shared resource are intertwined; they both influence how the provider's reputation is assessed.…”
Section: Privacy and Usersmentioning
confidence: 99%